PERLINDUNGAN HUKUM TERHADAP PEMBELA HAK ASASI MANUSIA PERSPEKTIF TEORI ALASAN PENGHAPUS PIDANA - Moch. Choirul Rizal (Arena Hukum, 2023)
Legal protection of human rights defenders in Indonesia is at an alarming point. This sociolegal study focused on the objective conditions of legal protection for human rights defenders and the legal protection for human rights defenders from a theoretical perspective on the reasons for erasers punishment. The results are human rights defenders still experience arrests, shootings, clashes and torture. There are also several criminal law policies that have the potential to violate the rights and guarantees of legal protection for human rights defenders. Second, "the theory of lesser evils" can be used as a basis for providing legal protection to human rights defenders. As long as the actions of human rights defenders are to implement Article 67 of Law No. 32 of 2009, for example, human rights defenders can be seen as "implementing the laws and regulations" and protected by Article 66 of Law No. 32 of 2009, so that Article 50 of the Criminal Code can be applied as an excuse to eradicate crimes. In the future, guidelines for the criminalization of human rights defenders when dealing with criminal case settlement processes are also needed.